Ex cathedra/Ex auditorio - Davidsen, Ole (Religionsvidenskabeligt Tidsskrift, 1982)
In his dissertation “Den Kristne Grundfortælling” (The Fundamental Christian Story), Svend Bjerg undertakes the task of defending a thesis according to which Christianity and theology, in a fundamental sense, depend upon the use of “story” (or: narrative). True to his convictions Bjerg argues that theological reflections should be based on the stories themselves, in the last instances on the fundamental Christian story. Only by such an anchorage will be able to avoid free-floating theology. In his examination – ex auditorio – the author does not raise objections to this thesis, but criticizes Bjerg for lacking a determination of what “the fundamental Christian story” is, which is defined as an actually available story. The fundamental story of Christianity, i.e. that Christian story – among others – which forms the foundation of Christianity, and, subsequently, constitutes the basis of a solid theology, is never pointed out. So, Bjerg has – ex cathedra – postulated that theology depends on “story”, but he has not been able to prove it.